2016
DOI: 10.1144/jgs2015-119
|View full text |Cite
|
Sign up to set email alerts
|

Ground-penetrating radar stratigraphy and dynamics of megaflood gravel dunes

Abstract: Ground-penetrating radar was used to elucidate the stratigraphy of late Pleistocene gravel dunes in the Altai Mountains of southern Siberia that formed when a lake emptied as a result of ice-dam failure. Survey-lines across dunes had a resolution of decimetres, with depth penetration of 20 m. The reflections identify bounding surfaces and radar facies. Two classes of unconformities are identified: (1) an erosional unconformity at the base of the dunes; (2) steeply inclined unconformities that truncate underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…13c). As for Aktru, having subcritical flow at Kuray is in accordance with the prior identification of these bedforms as dunes (Carling et al, 2016). Carling et al (2016) related between three and five reactivation surfaces within the Kuray dunes to either intermittency in sediment transport during a single event or due to several distinct flood events reactivating the dunes.…”
Section: The Formation Of Gravel-dune Fieldssupporting
confidence: 83%
See 2 more Smart Citations
“…13c). As for Aktru, having subcritical flow at Kuray is in accordance with the prior identification of these bedforms as dunes (Carling et al, 2016). Carling et al (2016) related between three and five reactivation surfaces within the Kuray dunes to either intermittency in sediment transport during a single event or due to several distinct flood events reactivating the dunes.…”
Section: The Formation Of Gravel-dune Fieldssupporting
confidence: 83%
“…As for Aktru, having subcritical flow at Kuray is in accordance with the prior identification of these bedforms as dunes (Carling et al, 2016). Carling et al (2016) related between three and five reactivation surfaces within the Kuray dunes to either intermittency in sediment transport during a single event or due to several distinct flood events reactivating the dunes. Due to the short period of potential transport modelled by Bohorquez et al (2016, 1.3 hours), Carling et al (2016) concluded that several floods were probably responsible for the reactivation surfaces.…”
Section: The Formation Of Gravel-dune Fieldssupporting
confidence: 83%
See 1 more Smart Citation
“…The imprints of the floods are numerous including impressive morphological features such as mega-sized bedforms and thick coarsegrained deposits (e.g. Parde, 1942;Bretz et al, 1956;Malde, 1968;Baker, 1973;Carling, 1996Carling, , 2013Maizels, 1997;Carling et al, 2016;Winsemann et al, 2016). Unravelling the influence of such extreme events on present-day landscapes is not always easy due to their enormous scale.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ground penetrating radar (GPR), which allows for rapid and real-time measurements, has received great attention for nondestructive testing (NDT). This technique has been applied for pavement investigation [ 4 ], geological exploration [ 5 ], civil engineering [ 6 ], subsurface archaeological investigation [ 7 ] and thin-layer thickness estimation [ 8 ]. In the forestry field, GPR has provided an important method of root system architecture reconstruction [ 9 ], root diameter or biomass estimation [ 10 ], and moisture content [ 11 ].…”
Section: Introductionmentioning
confidence: 99%